Penegakan Hukum Mahar Politik dalam Pilpres 2019 Ditinjau dari Politik Hukum Pidana - Irwan Hafid; Dendy Prasetyo Nugroho (Jurnal Adhyasta Pemilu, 2019)
The issue of political dowry, relatively, becomes a sustainable warning of problems in every general election in Indonesia. Such as the issue of Sandiaga Uno, who provided political dowry in the 2019 presidential election. The allegation was started by the Deputy of General-secretary of the Party of Democrat, Andi Arief, who stated that Sandiaga Uno had provided 500 billion rupiahs to PAN and PKS respectively so that those two parties would support him to nominate as the Candidate of Vice President for Prabowo Subianto. Political dowry has been a serious issue and almost constantly becomes an interesting topic to be reported and studied in every general election. Although it is popular, the issue of political dowry is a case that is relatively difficult to prove its truth (court decisions). In fact, explicitly, political dowry has been regulated in Article 228 on Law Number 7 of 2017 concerning the General Election (Election Law). However, it does not expressly provide a deterrent effect to the political dowry actors. This reality becomes the basis of encouragement in conducting this research. The theory used in this research is legal politics and law enforcement. While the method used is normative legal research with a statutory, conceptual, and comparative approach. The output of this paper is that the handling of political dowry cases in the presidential election needs a serious concern. And then, the regulation on sanctions, which still be administrative in nature, against the actors of political dowry in the Election Law is considered to be inappropriate. So that criminal policy is needed to strengthen the law enforcement and strict legal instruments against criminal acts of political dowry in the future election (ius constituendum).